THE IMPLEMENTATION OF INTERNATIONAL FINANCIAL FOR REPORTING STANDARDS (IFRS) ON NET INCOME OF PUBLIC COMPANIES IN INDONESIA - Mariana, Mariana; Liza, Laisa (IAIN Lhokseumawe, 2024)
Adoption of IFRS (International Financial Reporting Standards) is considered as a solution to increase credibility and transparency in financial reporting and strengthen the global financial architecture. Adjustments from IFRS to Financial Accounting Standards (SAK) in Indonesia are carried out by the Financial Accounting Standards Board (DSAK). This research aims to assess the importance of profit value after IFRS implementation in non-financial companies listed on the Indonesia Stock Exchange. Data from 2018-2022 (after IFRS adoption) and 2006-2008 (before IFRS adoption) were analyzed. The variables used include earnings relevance, measured by share price, changes in earnings, earnings per share, and book value of equity. The paired sample T-test in SPSS version 25 was used for analysis. The research results show an increase in the relevance of earnings after the adoption of IFRS. Although there is no significant difference in stock prices before and after IFRS adoption, there is an average decline after IFRS adoption. However, significant differences in changes in earnings, earnings per share, and book value of equity were identified, reflecting the impact of IFRS adoption on earnings relevance.